2020
DOI: 10.1016/j.rbmo.2020.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, promotion and pricing of three IVF add-ons on fertility clinic websites

Abstract: Research question How are IVF clinic websites advertising three common IVF add-ons: assisted hatching, time-lapse embryo imaging and preimplantation genetic testing for aneuploidies (PGT-A)? Design The Human Fertilisation and Embryology Authority ‘Choose a fertility clinic‘ website service was used to identify IVF clinics and their websites. Assisted hatching, time-lapse embryo imaging and PGT-A were examined to determine which websites advertised them, what price they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
(30 reference statements)
1
34
0
Order By: Relevance
“…Scholars suggest that the commercialisation of add-ons is part of a wider speculative turn in IVF, with the sector attracting an increasing amount of venture capital and private equity investment ( Van de Wiel, 2019 , 2020 , 2020 ). Studies reviewing how add-ons are offered by British IVF clinics ( Spencer et al, 2016 ; Van de Wiel et al, 2020 ) criticise the lack of clarity regarding their safety and effectiveness. For these reasons, some IVF professionals are critical toward the uncontrolled spread of add-ons ( Rutherford, 2017 ; Repping, 2019 ) and advocate caution in offering potentially non-beneficial add-ons to vulnerable patients without solid evidence ( Harper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars suggest that the commercialisation of add-ons is part of a wider speculative turn in IVF, with the sector attracting an increasing amount of venture capital and private equity investment ( Van de Wiel, 2019 , 2020 , 2020 ). Studies reviewing how add-ons are offered by British IVF clinics ( Spencer et al, 2016 ; Van de Wiel et al, 2020 ) criticise the lack of clarity regarding their safety and effectiveness. For these reasons, some IVF professionals are critical toward the uncontrolled spread of add-ons ( Rutherford, 2017 ; Repping, 2019 ) and advocate caution in offering potentially non-beneficial add-ons to vulnerable patients without solid evidence ( Harper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this study found that clinics advertising complementary therapies were in the minority, and complementary therapies were not offered at the same level as laboratory or clinical add-ons ( van de Wiel et al, 2020 ), the HFEA patient survey found that a significant proportion of patients incorporate complementary therapies into their IVF journey ( HFEA, 2018 ). There are two possible reasons for this observed discrepancy.…”
Section: Discussionmentioning
confidence: 96%
“…An in-vitro fertilization (IVF) add-on is defined as any technique that is a variation of, or add-on to, the ‘normal’ IVF cycle. This includes laboratory, clinical and complementary treatments ( van de Wiel et al, 2020 ). With increasing demand for IVF, and competition between clinics to attract patients, it is unsurprising that a number of treatment add-ons are marketed to patients ( Harper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients and clinicians tend to be willing to try diverse add-ons after several attempts have failed. However, their added costs should not be dismissed if their use is not justified by a proven increase in possibility to achieve a successful pregnancy [ 31 , 32 ]. Bearing in mind the controversy around the introduction of add-ons into the clinical practice without proper security and regulatory reviews [ 33 , 34 ], it is of utmost importance that clinicians are provided with reliable information resulting from carefully designed research, both prospective (randomized clinical trials or RCTs) and retrospective, making use of powerful statistical tools, proper designs, and bias control [ 35 ], to ensure that patients receive treatments catered to their needs and situation.…”
Section: Discussionmentioning
confidence: 99%